Factors Enhancing Virulence Response of Agrobacteria in Cucumber (Cucumis sativus L.) (The Agriculturists, 2010)
The virulence response of five wild type Agrobacterium tumefaciens (tumorigenic) strains and five wild type A. rhizogenes (oncogenic) strains was studied in cucumber (Cucumis sativus L.), cv. Spring Swallow. Several physical and chemical factors e.g. Agrobacterium strains, tissue type (stem and petiole tissues), light intensity, dark incubation, concentrations of acetosyringone (a phenolic compound) were tested. The virulent response of Agrobacteria was found to be depend on plant tissue type, Agrobacterium strain, tissue-Agrobacterium interaction and both chemical-physical factors. Specific light intensity, 2500-lux, as well as the acetosyringone concentration, 20-mM, played important role in virulence response. Among the different strains, LBA 4404 and 15834 were highly virulent to cucumber compared to the other strains tested. A. tumefaciens strains A348 and A281 were failed to initiate crown galls in both stem and petiole tissues, however, in the presence of acetosyringone they produced crown galls. Similarly, A. rhizogenes strain A4 initiated hairy roots in the presence of acetosyringone. All developed crown galls and hairy roots showed an autonomous growth on a hormone free medium containing cefatoxime. Thus, enhancement of virulence response was not only dependent on Agrobacterium strains, but also on particular physical and chemical factors also play vital role.